Potencialidad de la producción de biogas a partir de la excreta animal en la florícola VIBRAFLOWERS 2013. Propuesta del diseño tecnológico de un mezclador para aprovechar el metano en motores de combustión interna. - Quiroz Erazo, Leonidas Antonio (2013)
This study is based on the theoretical basis of the potential of biogas production from animal excreta at “VIBRAFLOWERS” flower greenhouse and use of methane that could be generated by designing a mixer in the internal combustion engine to take advantage of the biomass generated by their livestock activities in the flower greenhouse in production of electricity, cleanliness of cattle, etc. It is an alternative and efficient energy which reduces the environmental pollution generated by the biomass or unburned methane. The field research and literature evidenced the little exploitation of this energy for daily work place. Showing technical and economic useful data for the technical design proposed a mixer to get methane in internal combustion engines as an alternative energy. It starts from an experimental study where is determined the potential for the generation excreted product of its daily activities, so that the evaluation of biomass for biogas production in the flower greenhouse is made with the intention of providing with procedures that decrease the negative environmental footprint, the mixer was designed considering both environmental and mechanical variables, besides it is correlated the obtained data with the analysis of the predominant incidence such as speed, pressure and relation of gaseous fuel and air mixture into simulation on the software ANSYS and SOLIDWORS programs, where they are considered the manufacturing materials and in this way to obtain parameters of working almost close to the reality, providing reliability to the research operation and construction and test execution functionality of the mixer for its installation in the internal combustion engine.